Awake intubation with Bonfils retromolar fiberscope in patient under dexmedetomidine sedation: 7 case reports (2009)
Acording to the 'Practice Guidelines for management of a difficult airway', and several algorithnes, an awake intubation is considered the first method to secure a suspected difficult airway. During last years the awake intubation was performed by flexible fiberoptic laringoscopy or with a rigid stylet. Within the last decade, many new devices have been developed to assist anesthesiologist with both routine and difficult airway management, one of wich is the Bonfils Retromolar Intubacion Fiberscope. It is a semi-rigid optical stylet 40 cm. long of 5,0 external diameter and a tip curvature of 40 degrees; the adult stylet can accommodate a 6,5 mm. endotracheal tube and sliding it in the superior airway, it is possible to entubate the glottis under direct vision. We present seven case report with difficult airway, managed with dexmedotomidine using the Bonfils retromolar fiberscope without topical anesthetic.